El domador de pulgas (The Flea Tames) by Max Jiménez: An approach to his philosophical thought - Arce, Carla (2018)
El domador de pulgas (The Flea Tames)(1936), a novel by Max Jiménez Huete (1900-1947), a Costa Rican writer and artist, represents the universality of his thought in relation to human disappointment. Jiménez makes a fictional symbolization of humanity as a result of the loss of social values.